The concept of objects of civil turnover - A. S. Slipchenko Slipchenko (Bulletin of Kharkiv National University of Internal Affairs)
In the conditions of the current world crisis, the urgent need for the further development of Ukraine in the conditions of a market economy and its economic integration with the European Union, the isues of legal regulation of civil turnover are gaining relevance. To solve them, it is necessary to define the concept of the object of civil turnover, because, as it is rightly noted in the legal literature, it is important for a lawyer to understand not only whether a certain substrate is an object of civil rights, but also whether it is an object civil turnover. The first allows to determine the content of the legal relationship that could be formed in relation to the corresponding good. The second makes it possible to determine the range of circumstances that allow or prevent the transition, transfer, alienation of such goods in society.